Feminino velado: a recepção da telenovela por mães e filhas das classes populares - Silva, Renata Córdova da (2011)
This is a study of telenovela reception Passione conducted with mothers and daughters of working classes empirically that articulates the categories of gender, social class and generation. The goal is to understand how the receptors work out his notion of the feminine from the telenovela Passione. For this, the research is based on Latin American cultural studies, mainly on the Theory of Mediations, of Jesús Martín-Barbero. The methodology combines a rereading of the model encoding/decoding of Stuart Hall, made by Ronsini et al (2009), and critical ethnography of the reception (RONSINI, 2010). The results show that despite the telenovelas present several possibilities for feminine, domestic space is still portrayed as essentially linked to women. This discourse is fully assimilated by those mothers and partly by their daughters who not so easily accept the separation between the public sphere for men and women to the private sphere. These findings probably are due to their higher level of education when compared with educational level of the mothers. Motherhood, however, remains a priority for most respondents.